2005
DOI: 10.1103/physrevc.71.059803
|View full text |Cite
|
Sign up to set email alerts
|

Reply to “Comment on ‘Hadronic production of thermal photons’”

Abstract: We address a recent comment by Alam et al. [Phys. Rev. C 71, 059802 (2005)], on our work of thermal photon emission rates from hadronic matter. Specifically, we explain how t-channel ω exchange in the πρ → πγ reaction arises as a dominant contribution to the rates at high energy and why hadronic form factors cannot be neglected in this assessment. [2], namely that t-channel ω exchange is a dominant source of high-energy photons from a thermal hadronic gas. In their reasoning, they intentionally omit the insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This expression may be easily generalized from Eqs. (26,25,38) The δ-function δ(l ⊥ + l q ⊥ ) is shifted to δ(l q ⊥ ) and is then broadened by multiple scattering as in Eq. (38).…”
Section: Multiple Scattering Of Quark and Radiated Gluonmentioning
confidence: 99%
See 1 more Smart Citation
“…This expression may be easily generalized from Eqs. (26,25,38) The δ-function δ(l ⊥ + l q ⊥ ) is shifted to δ(l q ⊥ ) and is then broadened by multiple scattering as in Eq. (38).…”
Section: Multiple Scattering Of Quark and Radiated Gluonmentioning
confidence: 99%
“…In a hydrodynamical evolution, the local temperature T is known. The rates for a hard parton to decay into a quark or a gluon are then calculated using the local temperatures and the change in the distribution is computed using the Fokker-Planck equation over all paths [38,96].…”
Section: Energy Loss In a Non-uniform Mediummentioning
confidence: 99%
“…The data indicate that there may be a small suppression at high p T , but there is no indication of the expected in-medium suppression at lower p T , albeit with large uncertainties. It has also been suggested that quark-photon conversions in the medium could lead to an enhancement of direct photon production at intermediate p T [33]. There is no evidence for such an enhancement in the data.…”
Section: Non-interacting Probes: Photonsmentioning
confidence: 82%
“…We compare the π 0 v 2 to two models, a calculation done by Turbide et al [8] (using an Arnold-Moore-Yaffe (AMY) formalism [9]) and the Molnar Parton Cascade (MPC) model [10]. Figure 3 shows calculations from these models, plotted alongside data for similar centralities.…”
Section: Resultsmentioning
confidence: 99%